Pie Tepung Ubi Ungu Dan Kacang Merah Alternatif Makanan Selingan Bagi Penderita DM Tipe 2 - Ma'rifah, Bahriyatul; Astuti, Erna Tri; Kusumawati, Dewi (JURNAL RISET GIZI, 2024)
Background: Type-2 diabetes mellitus (DM) is a metabolic syndrome characterized by hyperglycemia due to oxidative stress. Efforts to reduce oxidative stress may include consuming snacks with high antioxidant activity and flavonoids made from purple sweet potato flour and kidney bean flour.Objectives: To determine the effects of the purple sweet potato flour and kidney bean flour ratio on the organoleptic properties (hedonic and hedonic quality tests), antioxidant activity, flavonoid content, and estimated selling price per serving of pie as an alternative snack for patients with type-2 DM.Method: Used a Complete Randomized Design (CRD) with three formulations of purple sweet potato flour and kidney bean flour: F1 (60%:40%), F2 (70%:30%), and F3 (80%:20%). Statistical analysis of antioxidant activity and flavonoids was performed using ANOVA and Duncan’s test. Meanwhile, organoleptic properties were examined using Kruskal-Wallis and Mann-Whitney tests.Results: There was significant effect of the purple sweet potato flour and kidney bean flour ratio on antioxidant activity, flavonoid content, and hedonic tests (color and aroma) (p0.05). However, no significant effect was found on hedonic taste, texture, mouthfeel, aftertaste, overall preference, and all hedonic quality (p0.05). The antioxidant activity of the pie formulations F1, F2, and F3 was weak, namely 6.539 mg/ml, 8.158 mg/ml, and 7.679 mg/ml, respectively. The flavonoid content was also low, accounting for 0.74%, 0.52%, and 0.80%, respectively. The selected formulation was F3 with hedonic quality of brown color, slightly weak sweet taste, weak bitter taste, distinctive flour taste, and medium aroma, texture, mouthfeel, and aftertaste. The estimated selling price per serving (85g) of F3 was IDR 3,768.26Conclusion: The selected formulation (F3) of  pie can used as alternative snack for patients with type-2 DM.